P286 Sustained improvement in health-related quality of life outcomes in patients with Ulcerative Colitis with long-term tofacitinib treatment in the open-label extension study, OCTAVE Open. (21st January 2022) - Biedermann, L; Dubinsky, M C; Vermeire, S; Fellmann, M; Gardiner, S; Hur, P; Mundayat, R; Panés, J; Rubin, D T
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). Tofacitinib induction and maintenance therapy has previously been shown to improve health-related quality of life (HRQoL) outcomes. Here, we present HRQoL data from patients (pts) with UC who received tofacitinib 5 or 10 mg twice daily (BID) in the Phase 3 open-label, long-term extension (OLE) study (OCTAVE Open; NCT01470612), up to Month (M)72. Methods: Proportions of pts with an Inflammatory Bowel Disease Questionnaire (IBDQ) total score ≥170, and EuroQol-5D (EQ-5D) and Short Form-36 Health Survey (SF-36) scores were analysed up to M72 in 4 subpopulations in the OLE study: 'maintenance remitters' completed OCTAVE Sustain in remission and received tofacitinib 5 mg BID in the OLE study; in contrast, 'maintenance treatment failures' (induction responders who experienced treatment failure), 'maintenance non-remitters' and 'induction non-responders (IndNR)' received tofacitinib 10 mg BID in the OLE study (Figure 1). Data were analysed for each subpopulation overall and stratified by prior tumour necrosis factor inhibitor (TNFi) failure, prior immunosuppressant failure and baseline corticosteroid use. Results: Baseline demographics and clinical characteristics for each subpopulation are shown in Table 1. Among the 163 maintenance remitters, HRQoL outcomes were maintained up to M72: 80.0% of pts had an IBDQ total score ≥170 (Figure 1); changes from baseline in EQ-5D scores up to M72 and SF-36 scores up to M33 were minimal (eg M72 EQ-5D utility score -0.07 [standard deviation 0.10]; M33 SF-36 physical functioning score -1.3 [8.3]). Among pts continuing long-term tofacitinib treatment, improvement in IBDQ total score was maintained/achieved by M2 (first post-baseline assessment), and was stable up to M72, with maintenance treatment failures and IndNR subpopulations experiencing the largest improvements from baseline (Figure 1). Similar trends were observed for improvement in EQ-5D and SF-36 scores. Improvements in HRQoL outcomes were independent of prior TNFi failure, prior immunosuppressant failure or baseline corticosteroid use, eg in maintenance remitters with prior TNFi failure, 90.9% of pts had IBDQ total score ≥170 at M60 vs 88.9% of pts without prior TNFi failure. Conclusion: Sustained beneficial effects in HRQoL were observed among pts continuing long-term tofacitinib treatment in OCTAVE Open. In maintenance remitters, improvements in all HRQoL outcomes were maintained with tofacitinib therapy. In pts who entered the OLE study not in remission and received tofacitinib 10 mg BID, HRQoL improvements were observed within the first 2 months, and were maintained up to M72, regardless of treatment history including prior TNFi failure.